THE AESTHETIC EVALUATION AND MAPPING OF LANDSCAPES OF LAKE SEVAN FOR DEVELOPING ITS RECREATION (Proceedings of the YSU C: Geological and Geographical Sciences, 2014)
One of the highlights of the research during the aesthetic evaluation of the landscapes is the classification of natural territorial complexes. On the basis of evaluation should be the expressiveness of the component. In other words, the components of the landscape that attract tourists should be in the foreground. Such components are relief, water facilities, vegetation, as well as anthropogenic complexes.
Keywords: relief; recreation; classification; nature landscape; Sevan Lake; water facility